Speaking Migrant Tongues in Edwin Thumbooâ€™s Poetry - Valles, Nanyang Technological University, Singapore, Eric Tinsay (Asiatic: IIUM Journal of English Language and Literature, 2013)
Singaporeâ€™s unofficial poet laureate, Edwin Thumboo, is best-known for poems celebrating nationhood. Not much critical attention has been given to his lyrics on the plight of migrants who are seeking a new identity. The quintessential Singaporean poem on nationhood, â€œUlysses by the Merlionâ€ (Reflecting on the Merlion 18-19) takes the objective viewpoint of a traveller who observes the settling down of itinerant peoples. The migrant is, in fact, a motif that is juxtaposed alongside the nation in many of Thumbooâ€™s works, from â€œThe Exileâ€ (20-21) in Gods Can Die to â€œUncle Never Knewâ€ (19-20) in Still Travelling. Thumboo shows how the migrantâ€™s voice, like the nationalistâ€™s, may clash with the dominant or official culture. In so doing, Thumboo gives utterance to his or her feelings and beliefs as well as suggests cultural improvisation as a means to convert the lyric into a means of building a nation and nurturing the individual other. Â  Â  In this paper, I will apply ethical concepts and aesthetic strategies outlined by Zhou Xiaojing in her study entitled The Ethics and Poetics of Alterity in Asian-American Poetry. She said that Asian-Americans differ because of their â€œinherent cultural otherness and subsequent political and cultural marginalization, and because of their apparently successful assimilationâ€ (1). I will explore how Zhouâ€™s appropriation of Levinasian otherness may generate an appreciation of the migrantsâ€™ cosmopolitan experience and social critique in Thumbooâ€™s poetry. Otherness as irreducible is also a form of intervention in an adopted society. It requires new ways of looking and voicing the experiences of self and nationhood. This otherness opens up new possibilities for the use of language, imagery and poetic techniques.